A SIMPÁTICA HISTÓRIA DE MELIM-MELOSO: A REINVENÇÃO DE MALAZARTE - Flach, Alessandra Bittencourt (Organon, 2007)
In Tutaméia, Guimarães Rosa makes a synthesis of what characterizes better his work as a whole: he explores the universe of types like the cowboy, the jagunço, the sinhá, the ordinary man from the sertão who has a lot to say, whether through his experiences narration, or through his particular worldview. To achieve that, the author makes use of a linguistic technique very peculiar to him. One of the 40 narratives presented in the book, “Melim-Meloso”, is about the transcendence of this simple quotidian to a level of personal sublimation from the adventures of a wily type, following the model of the heroes from traditional oral short stories. The dialogue between Guimarães’s character and Pedro Malazarte from the folk stories, more than a rescue of an ancestral theme, is a proof of how erudite culture has appropriated and reinvented the popular universe.